Wear of metal-free resin composite crowns after three years in service - Zenthöfer, Andreas; Rammelsberg, Peter; Ohlmann, Brigitte (Dental materials journal, 2013)
To compare differences between the wear behavior of two types of metal-free resin composite crown with a control after three years in clinical service. Sixty-six participants needing one to three posterior single crowns were fitted with 120 crowns. Abutment teeth were randomly assigned to three groups: 40 resin composite crowns with fiber-reinforced framework, 40 resin composite crowns without fiber-reinforced framework, and 40 metal-ceramic crowns. To assess wear, gypsum replicas of the crowns were fabricated and scanned with a 3D laser scanner at baseline and after three years. Differences between the groups were analyzed by use of mixedeffects regression models. Wear of resin composite crowns with fiber-reinforced framework (p=0.0043) and resin composite crowns without framework (p=0.0246) was significantly greater than in the metal-ceramic group. Wear of metal-free resin composite crowns after three years was significantly greater than that of metal-ceramic crowns, but the wear was still clinically acceptable.